Fenton-like processes and adsorption using iron oxide-pillared clay with magnetic properties for organic compound mitigation - Tireli, Aline Auxiliadora; Guimarães, Iara do Rosário; Souza Terra, Júlio César de; Silva, Robson Rosa da [UNESP]; Guerreiro, Mario Cesar (Springer, 2015)
In this work, a new step was added to the classic route of iron-pillared clay obtention, resulting in a material with both magnetic and oxidative properties. The saturation of the material surface intercalated with trinuclear acetate-hydroxo iron (III) nitrate in glacial acetic acid atmosphere before heat treatment promoted magnetic phase formation (FePMAG). The material was characterized by Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), nitrogen adsorption/desorption isotherms, scanning electron microscopy coupled with energy dispersive spectroscopy (SEM/EDS), and X-ray photoelectron spectroscopy (XPS). FePMAG showed an increase of 0.57 nm in basal spacing which contributed to the specific surface area increase from 39.1 to 139.2 m(2)/g. The iron phase identified by XRD and XPS was maghemite, with a little presence of hematite formed by the trinuclear acetate-hydroxo iron (III) nitrate decomposition during heat treatment. In the adsorption tests, FePMAG displayed a good capacity for organic dye methylene blue (MB) removal, reaching 41 % at 150 min. Under photo-Fenton conditions, the material showed an excellent MB oxidation capacity, completely removing the color of the solution within 90 min. Identification of the oxidation products with lower molecular (m/z = 160, 220, and 369) mass was performed by electrospray ionization mass spectroscopy (ESI-MS).
Keywords: Pillared clay; Organic compound; Photo-Fenton; Oxidation mechanism